In Silico, In Vitro, and Pharmacokinetic Studies of UBMC-4, A Potential Novel Compound for Treating against Trypanosoma cruzi (2022)
ABSTRACT: : The lack of therapeutic alternatives for the treatment of Chagas disease, a neglected disease, drives the discovery of new drugs with trypanocidal activity. Consequently, we conducted in vitro studies using UBMC-4, a potential Trypanosoma cruzi AKT-like pleckstrin homology (PH) domain inhibitory compound found using bioinformatics tools. The half effective concentration (EC50) on intracellular amastigotes was determined at 1.85 ± 1 µM showing low cytotoxicity (LC50) > 40 µM on human cell lines tested. In order to study the lethal effect caused by the compound on epimastigotes, morphological changes were assessed by scanning and transmission electron microscopy. Progressive alterations such as flagellum inactivation, cell size reduction, nuclear structure alteration, condensation of chromatin towards the nuclear periphery, vacuole formation, and mitochondrial swelling with kinetoplast integrity loss were evidenced. In addition, apoptosis-like markers in T. cruzi were assessed by flow cytometry, demonstrating that the effect of UBMC-4 on T. cruzi AKT-like kinase reduced the tolerance to nutritional stress-triggered, apoptosis-like events, including DNA fragmentation, mitochondrial damage, and loss of plasma membrane integrity. After this, UBMC-4 was formulated for oral administration and pharmacokinetics were analyzed in a mouse model. Finally, upon oral administration of 200 mg/kg in mice, we found that a UBMC-4 plasma concentration remaining in circulation beyond 24 h after administration is well described by the two-compartment model. We conclude that UBMC-4 has an effective trypanocidal activity in vitro at low concentrations and this effect is evident in T. cruzi cell structures. In mice, UBMC-4 was well absorbed and reached plasma concentrations higher than the EC50, showing features that would aid in developing a new drug to treat Chagas disease